Lesbian, Gay, and Bisexual Adults: Childhood Gender Nonconformity, Childhood Trauma, and Sexual Victimization. Issue 3 (February 2019) - Bos, Henny; de Haas, Stans; Kuyper, Lisette
The present study examined whether the relationship between childhood gender nonconformity and sexual victimization in adulthood among lesbian, gay, and bisexual (LGB) same-sex attracted men and women is mediated by experiences with childhood trauma experiences by an adult family member. Data are based on a survey among same-sex attracted individuals ( N = 2, 352; 1, 396 men and 956 women; M age = 44.97) recruited from an online research panel. Participants completed an online questionnaire consisting of existing scales. Sixteen percent of the participants reported that they had experienced sexual victimization as an adult. There were gender differences: Men reported less childhood gender nonconformity and women more often reported experiences with childhood trauma by an adult family member and sexual victimization as an adult. Bootstrapped mediation analysis and follow-up moderated mediation analyses showed that childhood trauma significantly mediated the relation between childhood gender nonconformity and experiences of sexual victimization for men but not for women. In other words, for men higher levels of childhood gender nonconformity predicted experiences with childhood trauma by an adult family member, which in turn predicted the higher prevalence of sexual victimization. Implementations of these findings are that interventions aimed at increasing the social acceptance of gender nonconformity might also lower the levels of childhood trauma and sexual victimization among gay and bisexual men. Professionals working with children (and especially with boys) should be aware of the impact of gender nonconformity on childhood trauma and experiences of sexual victimization later in life.